Microbial Communities in Biocrusts Are Recruited From the Neighboring Sand at Coastal Dunes Along the Baltic Sea - Glaser, Karin; Van, Ahn Tu; Pushkareva, Ekaterina; Barrantes, Israel; Karsten, Ulf (Frontiers in Microbiology, 2022)
Biological soil crusts occur worldwide as pioneer communities stabilizing the soil surface. In coastal primary sand dunes, vascular plants cannot sustain due to scarce nutrients and the low-water-holding capacity of the sand sediment. Thus, besides planted dune grass, biocrusts are the only vegetation there. Although biocrusts can reach high coverage rates in coastal sand dunes, studies about their biodiversity are rare. Here, we present a comprehensive overview of the biodiversity of microorganisms in such biocrusts and the neighboring sand from sampling sites along the Baltic Sea coast. The biodiversity of Bacteria, Cyanobacteria, Fungi, and other microbial Eukaryota were assessed using high-throughput sequencing (HTS) with a mixture of universal and group-specific primers. The results showed that the biocrusts recruit their microorganisms mainly from the neighboring sand rather than supporting a universal biocrust microbiome. Although in biocrusts the taxa richness was lower than in sand, five times more co-occurrences were identified using network analysis. This study showed that by comparing neighboring bare surface substrates with biocrusts holds the potential to better understand biocrust development. In addition, the target sequencing approach helps outline potential biotic interactions between different microorganisms groups and identify key players during biocrust development.